Sosialisasi Pentingnya Melakukan Deteksi Dini Tanda Bahaya Pada Ibu Hamil di Puskesmas Kamonji Kota Palu - A. Fahira Nur (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Pregnancy and childbirth are natural events. Even though it is a natural event, sometimes pregnancy and childbirth are accompanied by risks in the form of complications for both the mother and baby. Complications of pregnancy, childbirth and postpartum are major health problems for women's health, because they are the biggest cause of maternal and infant mortality. The aim of this service is to socialize the importance of pregnancy checks to health workers in order to detect early danger signs of pregnancy. Data was collected through initial data observation and analysis of documents related to the socialization program. The results of this service activity show that the socialization program has been implemented well for pregnant women in the Kamonji Community Health Center working area and it has been proven that Antenatal Care visits have increased. During the process of this activity there were several obstacles such as pregnant women who were not willing to come to the activity location, pregnant women who happened to be busy with the socialization activity schedule. The final results show that pregnant women are aware of the importance of carrying out pregnancy checks with health workers to find out the danger signs of pregnancy. This activity is routinely carried out on an ongoing basis so that it can support health policy programs.